Efeitos do fator de crescimento epidermal, progesterona e melatonina no desenvolvimento, ultraestrutura e expressão gênica em folículos secundários bovinos cultivados in vitro - Paulino, Laís Raiane Feitosa Melo (2022)
The present study investigates the effects of epidermal growth factor (EGF), progesterone (experiment 1) and melatonin (experiment 2) on development, viability and gene expression in bovine secondary follicles cultured in vitro for 18 days. For this purpose, secondary follicles (~0.2 mm) were isolated from the ovarian cortex and individually cultured at 38.5°C, with 5% CO 2 in air, for 18 days, in TCM-199 + alone (control medium) or supplemented with 10 ng/ml progesterone, 10 ng/ml EGF or both EGF and progesterone (experiment 1). In experiments 2, follicles were cultured in TCM-199 + alone or supplemented with melatonin in different concentrations at 10 -11 , 10 - 9 , 10 -7 or 10 -5 M (phase 1), as well as in medium supplemented with 10 - 7 M melatonin, 10M luzindole or both (phase 2). These treatments were developed for growth, antrum formation, viability, ultrastructure and mRNA levels for H1FOO, GDF9, CCNB1, eIF4E and PARN (experiment 1) SOD, CAT, GPX1 and PRDX6 (experiment 2). In experiment 2, the expression of type 1A/B melatonin receptors in oocytes and granulosa cells in primordial, primary, secondary and antral follicles of bovines was also investigated. GDF9 and cyclin B1 in oocytes increased RNA expression for GDF9 and cyclin B1 in oocytes. In addition, mRNA levels for cMOS and GDF9 increased significantly with the addition of EGF. The ultrastructures maintained in all follicles maintained the granulosa cells maintained. The results of experiment 2 showed the expression of type 1A/B melatonin receptors in oocytes and granulosa cells in primordial, primary, secondary and antral follicles in cattle. In vitro studies showed that secondary follicles cultured in medium supplemented with melatonin at a concentration of 10 -7 M had significantly larger diameters than those cultured in other treatments. Furthermore, the presence of the melatonin receptor antagonist, luzindole, blocked the effects of this hormone on follicular growth and viability. Follicles cultured in medium containing only melatonin showed significantly higher rates of antrum formation. Follicles grown in medium containing only melatonin had higher levels of mRNA for CAT and SOD than those grown with luzindole or melatonin and luzindole. Luzindol alone or melatonin and luzindole also reduced mRNA levels for GPX1 in follicles in culture. In conclusion, EGF promotes the development of secondary follicles cultured in vitro for 18 days and increases the expression of cMOS and GDF9, while progesterone alone or in association with EGF has no positive effect on follicular growth. Melatonin promotes growth and antrum formation in cultured bovine follicles through its membrane-coupled receptors.